Pengaruh Pajak Kepemilikan Asing Dan Profitabilitas Terhadap Penerapan Transfer Pricing - Khairun Najwa; Youdhi Prayogo; Marissa Putriana (STEKOM PRESS, 2024)
This research aims to determine the effect of foreign ownership tax and profitability on the implementation of transfer pricing. This research uses a quantitative approach with secondary data in the form of data obtained from mining sector companies registered on the sharia securities list for the period (2017-2022). The sampling method uses purposive sampling with a sample consisting of 7 companies. This research uses data analysis methods, namely multiple linear regression and panel data processed with the SPSS application. The results of this research show that the tax and profitability variables do not have a significant effect on the application of transfer pricing, while foreign ownership has a positive and significant effect on the application of transfer pricing.